PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PROGRAM LINEAR DUA VARIABEL UNTUK KELAS XI SMA/MA - Nur' Alawia (Jurnal Edukasi dan Penelitian Matematika, 2022)
The implementation of the 2013 curriculum in schools still encounters many obstacles during learning. The learning process is not optimal and the LKPD as a supporter/support for the implementation of the lesson plans is not yet available. Educators have tried so that the learning objectives can be achieved optimally. However, the implementation of better learning in the 2013 curriculum has nor been implemented optimally. This is because students to tend to have difficulty solving problems about non-routine questions. This study aims to develop LKPD on two variable linear programming material that is valid, practical, and effective by using a Contextual Teaching and Learning (CTL) approach. This research is a type of development research using the Plomp development model which consists of 3 stages, namely preliminary research, prototyping phase, and assessment phase. The research subjects in this study were students of class XI SMAN 1 Kuantan Hilir who had been selected on a limited basis. The data collection instrument used in this study was in the form of a validation sheet filled out by several experts, a practical questionnaire, and a final test to test the effectiveness of the product that had been made. The results of these data are then analyzed using qualitative and quantitative analysis techniques. Based on the results of data analysis, it shows that the LKPD based on the CTL approach has met the valid criteria with a validity percentage of 85,11%, practical with a percentage of 86,66%, and effective with classical completeness of 83,33%. Keywords– student worksheet, contextual teaching and learning, valid, practical, effective